Systematics of the genus Scleroplax Rathbun, 1893 (Crustacea: Brachyura: Pinnotheridae) - Campos, Ernesto (Zootaxa, 2006)
The taxonomic status of the monotypic genus Scleroplax Rathbun, 1893, is evaluated and separated from other genera of the Pinnixa White, 1846, complex. Distinguishing characters of Scleroplax are a hard, subheptagonal and dorsally, highly convex carapace, and a third maxilliped with a propodus that extends to the end of the dactylus. The genera Scleroplax, Pinnixa, Austinixa Heard & Manning, 1997, Glassella Campos & Wicksten, 1997, Indopinnixa Manning & Morton, 1987, and Tetrias Rathbun, 1898, share a carapace than is wider than long and a distinct lateral exopod lobe on the third maxilliped, all of which may represent monophyletic characters. Updated information on the distribution and hosts of S. granulata Rathbun, 1893, indicate that the species now ranges from Vancouver Island, British Columbia, Canada to El Coyote estuary, Punta Abreojos, Baja California Sur, México. It inhabits burrows of the echiuroid Urechis caupo Fisher & MacGinitie, 1928, and the mud shrimps Neotrypaea californiensis (Dana, 1854), N. gigas (Dana, 1852) (new host record), Upogebia pugettensis (Dana, 1852), and occasionally U. macginiteorum Williams, 1986 (new host record).